"Shrink‐to‐Fit" Superhydrophobicity: Thermally‐Induced Microscale Wrinkling of Thin Hydrophobic Multilayers Fabricated on Flexible Shrink‐Wrap Substrates. (5th May 2013) - Manna, Uttam; Carter, Matthew C. D.; Lynn, David M.
<x xml:space="preserve">Abstract</x> An approach to the design of flexible superhydrophobic surfaces based on thermally induced wrinkling of thin, hydrophobic polymer multilayers on heat‐shrinkable polymer films is reported. This approach exploits shrinking processes common to "heat‐shrink" plastics, and can thus be used to create "shrink‐to‐fit" superhydrophobic coatings on complex surfaces, manipulate the dimensions and densities of patterned features, and promote heat‐activated repair of full‐thickness defects. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>